Analisis Kelayakan Usaha Agroindustri Tempe Hygiene sebagai Produk Unggulan di Rumah Kedelai Grobogan - Larasati, Ayu; Setiadi, Agus; Setiyawan, Hery (Universitas Galuh, 2025)
The feasibility analysis of a business is important to asses whether the business is viable or not to carried out. This research aims to analyze the feasibility the hygienic tempeh agroindustry bussines based on legal, technical and operational, management and human resources, market and marketing, social, environmental impact analysis (EIA), and financial aspects. The study was conducted at Grobogan Soybeans House, located in Grobogan Regency, Central Java. A case study method was employed, using purposive sampling with 11 respondents, consisting of 6 internal and 5 external parties. The analysis applied a descriptive -quantitative approach based on five years of bussines data (2019 – 2023). The result indicate the hygienic tempeh agroindustry is feasible based on all evaluated aspects. Total investment is IDR 241,449,126, with annual depreciation expenses of IDR 2,282,887. The average annual production cost was IDR 127,868,087, utilizing 6,645 kg of raw materials to produce 33,225 packs per year, with a sales volume of 33,059 packs. The price hygiene tempeh is IDR 6,000 per pack, the annual revenue was IDR 198,354,000, yielding a profit of IDR 70,485,913. Financial feasibility analysis indicated an NPV of IDR 23,367,681, an IRR of 16.50%, a PI of 1.10, and a payback period of 4 years, 4 months, and 21 days. Sensitivity analysis showed that only a 2.80% increase in production costs was not sensitive to changes (feasible). Scenarios involving a 28% rise in raw material costs or a 10% reduction in production were highly sensitive, meaning the business would suffer losses under these conditions.